The political economy of European monetary integration - SPAVENTA, L. (PSL Quarterly Review, 2013)
The launch of the EMS, far from being the result of deep economic thinking, was the somewhat unexpected outcome of political initiative. The rather casual economic debate that took place at the time is appraised by examining some problems that were at the centre of the negotiations in 1978. Some economic and technical arguments used in the debate were either correct, but missing the political point, or irrelevant. On the other hand, when the EMS belatedly started in March 1979, much of the political glamour had gone. Ten years of EMS have witnessed a subtler and more interesting form of interaction between politics and economics. JEL: E42, F15